Tobacco influence in heavy metals levels in head and neck cancer cases - Bandeira, Celso Muller [UNESP]; de Almeida, Adriana Ávila [UNESP]; Carta, Celina Faig Lima; Almeida, Alaor Aparecido [UNESP]; de Figueiredo, Fellipe Augusto Tocchini [UNESP]; Sandrim, Valeria Cristina [UNESP]; Gonçalves, Antonio José; Almeida, Janete Dias [UNESP] (Springer Nature, 2018)
Heavy metals intoxication is known to be risk factors for various diseases, including cancer. These metals may be presented in food and soil as well as in leaf and tobacco smoke. The aim of this study was to correlate the exposure to heavy metals stemming from tobacco and head and neck squamous cell carcinoma carcinogenesis. Analysis of lead, copper, manganese, arsenic, chromium, and cadmium by atomic absorption spectrophotometry was performed in whole blood samples from 91 patients: 68 smokers with oral cavity, pharynx, or laryngeal cancer; 8 non-smokers with oral or larynx cancer; and 15 non-cancer smokers with tobacco-related diseases (control group). No differences were found in metals quantifications, except a significant difference was observed (p = 0.0223) with higher mean in copper levels for non-smokers with cancer. The present study concluded, for the groups evaluated, it was not possible to prove the relationship between the studied metals in the development of the neoplasm. On the other hand, the results of copper demonstrated a correlation with smokers with cancer and lower levels of circulating copper.
Keywords: Carcinoma, squamous cell; Head and neck neoplasms; Metals, heavy; Tobacco